372 Short- And Long-Term Outcome of Pneumonectomy for Lung Cancer: 20 Years' Experience of a Single Centre. (4th May 2021) - Amran, R; Hussain, A; Din, A C; Cowen, M; Chaudhry, M; Loubani, M; Tentzeris, V; Qadri, S S
Abstract: Introduction: Surgery is the most important therapeutic modality for the treatment of primary lung cancer. Studies normally reported as 30-days or 90-days post-operative mortality or 5-years survival. However, survival for ≥10-years is rarely mentioned. Method: Retrospective data collection from a tertiary centre database was implemented which include patients who underwent pneumonectomy from January 1998 until November 2019. The data was analysed for short and long-term outcomes including their respective Thoracoscore. Results: 268 patients who had pneumonectomy were selected, in majority for lung cancer. 79.1% were male with mean age is 63. Overall operative mortality in this cohort was 4.9% while reported national mortality for pneumonectomy for lung cancer is 7%. No 30-days post-operative mortality in the last 5 years. The 5, 10- and 15-years survival rate for patients are 36.9%, 23.9% and 20.3% respectively. This showed significant increase in the survival rate for 5- and 10-years post-pneumonectomy in comparison to previous study. Long-term survival was better in female with age <70 years. The overall survival rate >15 years is 0.4%. Conclusions: This study shows that our operative mortality for pneumonectomy is significantly lower (30% less) than national mortality. This confirms that pneumonectomy is still an effective modality in the treatment of lung cancer.